Linear Parameter-Varying Versus Linear Time-Invariant Reduced-Order Controller Design for Turboprop Aircraft Dynamics - Widowati Widowati; Bambang Riyanto; Hari Muhammad (Journal of Engineering and Technological Sciences, 2012)
The  applicability  of  parameter-varying  reduced-order  controllers  to aircraft  models  is  proposed.  A  generalization  of  the  balanced  singular perturbation method of the linear time-invariant (LTI) system was used to reduce the order of  the  linear parameter-varying (LPV) system. Based on the reducedorder model, a  low-order  LPV  controller  was  designed  using  the Hâˆž synthesis technique.  The  performance  of  the  reduced-order  controller  was  examined  by applying  it  to  the  lateral-directional  control  of  a  20th-order  aircraft  model. Furthermore, the time responses of the closed-loop system with  several reducedorder LPV controllers and  a  reduced-order LTI controller  were  compared.  The simulation results  show that an  ,  8th -order LPV controller can maintain stability and  provide  the  same  level  of  closed-loop  system  performance  as  a  full-order LPV  controller.  This  was  not  the  case  with  the  reduced-order  LTI  controller, which  cannot  maintain  stability  and  performance  for  all  allowable  parameter trajectories.